Peripherality and the impact of SME takeovers - James Foreman-Peck; Tom Nicholls (Cardiff University, Cardiff Business School, 2008)
If large companies buy small dynamic enterprises, and move them to the headquarters' location or elsewhere, the process could suppress regional, or dependent, economy income and productivity. We investigate this hypothesis by analysing around 2 million observations of the UK enterprise- level Business Structure Database. Contrary to the experience of large firms, more productive small businesses are more subject to takeover. In addition, SMEs that have been acquired are also more likely to both exit and relocate to another region. This last finding however cuts both ways; a peripheral region or country may receive post-merger companies as well as lose them. With the exception of the core of London and the South East, British regions achieve an approximate numerical balance of relocations from SME takeovers.
Keywords: L23; D21; R11; 330; SMEs; takeovers; regional development; exits; relocations; Großunternehmen; Übernahme; KMU; Produktivität; Betrieblicher Standort; Periphere Region; Regionale Entwicklung; Großbritannien